Bioactive materials for pulpotomies in primary dentition: literature review - Guevara Purizaca, Nayda Mirelly (2025)
There is a growing demand for increasingly biocompatible materials, especially for pulp therapies in children. In today's market, biomaterials such as mineral trioxide aggregate (MTA) and Biodentine have demonstrated high bioactive properties. However, no material has yet been identified that optimally meets all clinical requirements, due to factors such as biocompatibility, pulp repair potential, among others. The objective of this literature review was to determine the clinical and radiographic success rate of bioactive materials in pulpotomies, compared to the use of conventional materials. Additionally, the preferred final restorative material used after the application of the bioactive material was identified. PubMed, Scopus, ScienceDirect, Virtual Health Library, EBSCOHost, and ProQuest databases were used. The search included publications up to May 25, 2024, following PRISMA guidelines. Out of a total of 857 articles identified, twelve met the inclusion criteria and were selected for analysis. Subsequently, these studies underwent a control review to evaluate the results of pulp treatment: eleven were considered at the first year of follow-up and only one at the second year. The use of bioactive materials, such as Biodentine and calcium silicate cements, represents a significant advance in dentistry. These materials are easy to handle, set faster, and have a lower risk of discoloration than MTA.